A Nationwide Survey on the Facilities and Personnel for Endoscopic Sedation: Results from 50 Qualified Endoscopy Units of Teaching Hospitals Accredited by the Korean Society of Gastrointestinal Endoscopy (KSGE) - Seon-Young Park; Jun Kyu Lee; Jung-Wook Kim; Tae Hee Lee; Chang-Hwan Park; Jae-Yong Jang; Byung-Wook Kim; Byung Ik Jang; the Quality management and Endoscopic sedation committee of Korean Society of Gastrointestinal Endoscopy (KSGE) (Korean Society of Gastrointestinal Endoscopy, 2021)
Background/Aims This study aimed to determine the current status of facilities, equipment, and personnel for endoscopic sedation from endoscopy units of representative hospitals in South Korea. Methods A questionnaire survey was conducted on 50 qualified endoscopy units accredited by the Korean Society of Gastrointestinal Endoscopy. Results All included endoscopy units had regulations and educational programs regarding sedation training for endoscopists and nursing personnel. There present one assisting nurse during endoscopy in 35 units (70%) and at least two nurses in 12 units (24.0%). All endoscopy units had examination rooms equipped with oxygen supply and suction systems. Endoscopist-directed sedation was performed in 48 units (96.0%). Propofol-based sedation was the most used sedation method. All units had a separate recovery bay. The daily number of patients per bed was greater than 10 in 17 units (34.0%). In 26 (52.0%) units, a single nurse cared for ≥10 patients per day. All the units fulfilled the discharge criteria. Conclusions This study presents data regarding endoscopic sedation clinical practice in 50 endoscopy units in South Korea. This study presents the current status of endoscopic sedation clinical practice in 50 qualified endoscopy units accredited by the KSGE, which provide excellent quality management.